The scarcity-abundance relationship of mineral resources introducing some sustaintable aspects (2010)
The Planet has a large number of concentrations of minerals. However, the low price assigned to these resources and the principles of sustainable mining in the short term may cause limitations in the exploration and extraction of these resources in the immediate future and they affect the supply of minerals. The true accounts of non-renewable natural resources must be completed entering with the non market values associated to its exploitation. The environmental management tools (Exergetic Analisis and Life Cycle Assessment) are instruments to achieve this goal as outlined below.